Do innovation policies support micro and small enterprises to overcome barriers? - Alexandre de Vicente Bittar; Luiz Carlos Di Serio (Innovation & Management Review, 2023)
Purpose Micro and small enterprises (MSEs) play a crucial role in the development of any country by generating innovative ideas. However, they face inherent restrictions that hinder their innovation capabilities. It is essential to support innovation policies to overcome these barriers and foster innovation. This study aims to explore how innovation policies can reduce barriers to innovation in MSEs using the lens of innovation capabilities. Design/methodology/approach Through a multiple case study, the authors examined eight MSEs in S\~ao Paulo (Brazil) and five in Florence (Italy) to conduct this study. These countries share a similar level of importance when it comes to MSEs. Findings Current innovation policies could be more effective for MSEs if certain barriers they encounter are faced and resolved, such as limited financial resources and a scarcity of qualified workers. These barriers directly affect two key elements of their innovation capability: financial resources and human resources. Therefore, it is essential to develop innovation policies that target these elements directly to enable MSEs to overcome these obstacles and thrive. Originality/value This study aims to enhance the knowledge of how innovation policies can help alleviate obstacles to innovation and how they can influence the various components that comprise the innovation capability of MSEs. This research can be valuable for policymakers as it provides insight into which innovation policies impact each aspect of innovation capability, enabling them to choose the most suitable policy based on the specific needs and local circumstances of the MSEs.
Keywords: 650; Innovation capability; Innovation public policies; Micro and small enterprises